Análisis del control interno de supermercado Dismero S.A. de la ciudad de Babahoyo, periodo 2020 - Vera Freire, Dayana Mayli (2021)
The present study was carried out in order to analyze the internal control of the DISMERO S.A. supermarket. located in the city of Babahoyo. The methodology used was inductive. The analysis carried out left us as a result that the company is a victim of internal control mismanagement, focusing more specifically on inventories; For this case study, all the personnel working in the supermarket were taken as the population.